Harmaline Tremor: Underlying Mechanisms in a Potential Animal Model of Essential Tremor. (12th September 2012) - Handforth, Adrian
Background: Harmaline and harmine are tremorigenic β-carbolines that, on administration to experimental animals, induce an acute postural and kinetic tremor of axial and truncal musculature. This drug-induced action tremor has been proposed as a model of essential tremor. Here we review what is known about harmaline tremor. Methods: Using the terms harmaline and harmine on PubMed, we searched for papers describing the effects of these β-carbolines on mammalian tissue, animals, or humans. Results: Investigations over four decades have shown that harmaline induces rhythmic burst-firing activity in the medial and dorsal accessory inferior olivary nuclei that is transmitted via climbing fibers to Purkinje cells and to the deep cerebellar nuclei, then to brainstem and spinal cord motoneurons. The critical structures required for tremor expression are the inferior olive, climbing fibers, and the deep cerebellar nuclei; Purkinje cells are not required. Enhanced synaptic norepinephrine or blockade of ionic glutamate receptors suppresses tremor, whereas enhanced synaptic serotonin exacerbates tremor. Benzodiazepines and muscimol suppress tremor. Alcohol suppresses harmaline tremor but exacerbates harmaline-associated neural damage. Recent investigations on the mechanism of harmaline tremor have focused on the T-type calcium channel. Discussion: Like essential tremor, harmaline tremor involves the cerebellum, and classic medications for essential tremor have been found to suppress harmaline tremor, leading to utilization of the harmaline model for preclinical testing of antitremor drugs. Limitations are that the model is acute, unlike essential tremor, and only approximately half of the drugs reported to suppress harmaline tremor are subsequently found to suppress tremor in clinical trials.